2016
DOI: 10.1007/s00213-016-4368-9
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sex, estrous cycle, and social contact on cocaine and heroin self-administration in rats

Abstract: Rationale Preclinical studies indicate that gonadal hormones are important determinants of drug self-administration. To date, little is known about the influence of sex and estrous cycle on drug self-administration in ecologically relevant social contexts. Objective Examine the role of sex and estrous cycle in a rat model during cocaine and heroin self-administration with male-female and female-female social dyads. Methods Male and female virgin rats were trained to self-administer cocaine and heroin in op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
51
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 74 publications
12
51
2
Order By: Relevance
“…Importantly, the estrous cycle did not moderate the effects of social contact on cocaine self-administration, meaning that the effects of social contact described above were consistent across all four phases of estrous. We previously reported that social contact did not influence the effects of the estrous cycle on heroin self-administration (Lacy et al, 2016), suggesting that these findings are consistent across different drug classes. Collectively, these results suggest that ovarian hormones do not moderate the effects of social contact on measures of drug-seeking behavior.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Importantly, the estrous cycle did not moderate the effects of social contact on cocaine self-administration, meaning that the effects of social contact described above were consistent across all four phases of estrous. We previously reported that social contact did not influence the effects of the estrous cycle on heroin self-administration (Lacy et al, 2016), suggesting that these findings are consistent across different drug classes. Collectively, these results suggest that ovarian hormones do not moderate the effects of social contact on measures of drug-seeking behavior.…”
Section: Discussionsupporting
confidence: 58%
“…Using a multilevel multivariate analysis, responding was greatest during estrus, but the main effect of cycle failed to reach statistical significance ( p = .053). Previous studies have generally reported that cocaine seeking varies across the estrous cycle, with greater levels of responding observed during estrus (Feltenstein and See, 2007; Hecht et al, 1999; Lacy et al, 2016; Lynch et al, 2000; Roberts et al, 1989). Importantly, the estrous cycle did not moderate the effects of social contact on cocaine self-administration, meaning that the effects of social contact described above were consistent across all four phases of estrous.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a form of opioid‐mediated long‐term potentiation (LTP) in CA3 pyramidal cells contacted by mossy fibers (i.e., mossy fiber‐CA3 synapses) is present in high‐estrogen state female rats but not male rats (Harte‐Hargrove, Varga‐Wesson, Duffy, Milner, & Scharfman, ), suggesting that opioid‐associative learning processes could be enhanced in females in certain hormonal states. In support, cyclic fluctuations of estrogen levels have been shown to alter morphine sensitivity in women (Ribeiro‐Dasilva et al, ) and patterns of heroin self‐administration in rats (Lacy, Strickland, Feinstein, Robinson, & Smith, ).…”
Section: Introductionmentioning
confidence: 93%
“…There are effects of estrous cycle on heroin self-administration, with females reducing intake during proestrus, but exhibiting overall greater heroin intake than males [140]. Female rats also acquire heroin intake more rapidly than males [141,142].…”
Section: Mu-opioid Receptorsmentioning
confidence: 99%